Antioxidant and alpha-amylase inhibitory study of Sansevieria trifasciata Prain. leaves extract - Vivi Anggia; Lusi Putri Dwita; Istikomah Istikomah (Universitas Ahmad Dahlan, 2019)
Diabetes is one of the chronic diseases whose prevalence is increasing all over the world, including in Indonesia. Diabetes mellitus is characterized by high blood glucose levels that can be overcome by, for instance, inhibiting the alpha-amylase enzymes that play a role in carbohydrate hydrolysis. Several studies have proved that active antioxidant substances can also support the treatment of diabetic patients. Snake plant (Sansevieria trifasciata Prain.), or locally known as lidah mertua in Indonesia, is a traditional herbal used to treat diabetes. This study investigated the activity of the ethanol extract of S. trifasciata leaves in inhibiting Î±-amylase. The leaves were extracted by maceration with ethanol 70%, followed by phytochemical screening. The antioxidant activity was determined using the DPPH method, while the inhibition of Î±-amylase was measured using UV-Vis spectrophotometer at 524nm wavelength. The results showed that IC50 of the antioxidant activity was 1527.55 ppm, five times greater than the positive control, i.e., vitamin C. In the case of Î±-amylase enzyme, the IC50 of the ethanol extract of S. trifasciata leaves was 158.31 Î¼g/ml and 0.26 times more potential than acarbose. The study has proved that the crude extract of S. trifasciata leaves has the potential as one of the antidiabetics and antioxidants that can be studied further.Â